Charakteiystyka serologiczna populacji wsi Wielkie Drogi w pobliżu Krakowa - Swomowsfd, Piotr (Polskie Towarzystwo Antropologiczne, 1988)
SEROLOGICAL CHARACTERISTIC OF THE POPULATION OF WIELKCE DROGI VILLAGE NEAR CRACOW was made on the material of 83 persons of both sexes. The ABO, Rh(D) and Kell systems were examined. The frequencies of genes and phenotypes were evalusted and then the genetic intervals were computed for the investigated group in relation to other populations from Poland, Ukraine and Moravia.
SEROLOGICAL CHARACTERISTIC OF THE POPULATION OF WIELKCE DROGI VILLAGE NEAR CRACOW